EL CARIOTIPO DE BOMAREA PATINII BAKER SUBSP. PATINII (ALSTROEMERIACEAE) - Baeza, Carlos M.; Alzate, Fernando; Negritto, María; Ruiz, Eduardo (Gayana Botánica, 2008)
The karyotype of Bomarea patinii Baker subsp. patinii from Colombia was examined. The species has a karyotype 2n = 2x = 18, with a haploid formula 2m + 1sm + 5st + 1t-sat. The reported karyotype is asymmetric (AsI % = 75.51). The most of the chromosomes are acrocentric. This results are compared with other species of Bomarea from South America.